UKRAINIAN UNIVERSITY AT THE TIME OF EXPONENTIAL DEVELOPMENT - Ogneviuk, Victor (Educological discourse, 2018)
The article analyzes the influence of exponential development on the transformation of the modern Ukrainian university. The most significant, interdependent and influencing factors that lead to the creation of new models of the modern university's existence are singled out. Provided is a systematic analysis of the most acute problems inherent in Ukrainian universities in the context of the philosophy of exponential development which requires the university to continuously strive for excellence and maximum involvement in innovation and technological and socio-economic processes. Also, specific steps are suggested that will allow Ukrainian universities which do not meet the challenges of exponential development today, to overcome a deep mental, organizational, financial and innovation crisis. In particular, the emphasis is placed on certain legislative changes with the purposeful activities of executive authorities, local government and the academic community; overcoming stereotypical attitudes towards the state property, which leads to overburdening of the state by unusual functions and inefficient use of material and financial resources; the implementation of a mental revolution in the academic communities of universities, the attraction of renewed universities to socio-economic transformations on the basis of innovative technologies and philosophy of responsibility; overcoming the consequences of a reductionist worldview and the fragmentation of knowledge; provision of continuous technological re-equipment of universities; the development of new philosophical meanings of being for the newly created reality.